Case Report : A Woman 27 Year Old with Mosaic Turner Syndrome Associate Hypogonadotropic Hypogonadism - Cennikon Pakpahan; Bella Amanda; Berliana Hamidah; Rina Yudiwati (Universitas Airlangga, 2020)
Background: Turner syndrome is a chromosomal abnormality found in phenotypically women who have one intact X chromosome and the absence of second sex chromosomes. Case: The patient is a 27-year-old Javanese girl. At the age of 14 years, she came to the gynecology clinic with chief complaints of amenorrhea and then given cycloprogynova by the physcian, the complaint improved but menstruation did not appear in the following month did not return to the gynecologist for evaluation. At the age of 26, she returned to the gynecologist and then was given medicine to stimulate menstruation and was referred to an internist-endocrinologist because of a suspected hypothyroid. Then a few months later the patient returned to the gynecologist and then examined hormones, ultrasound, and karyotyping for evaluation as well as establishing the diagnosis. FT4 hormone examination results 0.87 ng / dl, TSHs 0.708 Uiu / mL, T3 (Total) 0.49 ng / mL, FSH 2.38 Miu / mL, LH 1.3 Miu / mL, prolactin 14.7 ng / ml, progesterone <0.10 ng / ml, estradiol <5 ng / ml indicates hypogonadotropic hypogonadism with hypothyroidism. Ultrasound results showed hypoplasia with uterine axis measuring 2.27 x 2.09 cm. Karyotyping result with 45x / 46xx indicate mosaic turner syndrome. Patients were given progestin, esthero and also thyrax for hormone replacement therapy. Discussion: Turner syndrome with hypogonadotropic hypgonadism is a rare variation of the turner syndrome. The definite cause is still uncertain. Some cases are usually accompanied by other hormone disorders such as thyroid and growth hormone. Conclusion: A 27-year-old woman with hypgonadotrophic hypgonadism associated with mosaic turner syndrome. The diagnosis is done by history taking, hormone examination, imaging, and karyotyping. treatment given progestin, estrogen, and thyrax.